ORAL SKUAMÖZ HÜCRELİ KARSİNOM: 3 OLGU SUNUMU VE LİTERATÜR DERLEMESİ - (:unkn) unknown (My University, 2018)
Skuamöz hücreli karsinom, oral kavitede en sık izlenen malignitedir. Ağız mukozasının her bölgesinde görülebilen bu karsinomlarda tütün ve alkol tüketimi önemli etkendir. Bu makalede son altı ay içinde kliniğimizde tanısı konan, lokalizasyonları bakımından farklı üç oral skuamöz hücreli karsinom olgusu literatür bilgileri doğrultusunda sunulmuştur

Squamous cell carcinoma is the most common malignancy affecting the oral cavity. Tobacco and alcohol consumption in these carcinomas can be seen in every region where the oral mucosa is an important factor. This article in the latest issue of our clinic diagnosed within six months in terms of localization of three different oral squamous cell carcinoma are presented in accordance with the literature
ORAL SQUAMOUS CELL CARCINOMA: 3 CASE REPORT AND REVIEW OF LITERATURE
Keywords: Diş Hekimliği